PELATIHAN PEMBELAJARAN CODING DALAM MERANCANG APLIKASI KALKULATOR SEDERHANA - Elnovreny, Jane; Sihotang , Siti Fatimah; Zuhri, Zuhri; Liwanda, Regina; Adellia, Juwita (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
A thorough understanding of stoichiometry is crucial for success in chemistry and related fields, such as biology, chemical engineering, and materials science. Without a solid understanding, students will struggle to interpret chemical equations, calculate the quantities of substances involved in reactions, and predict the outcome of reactions. However, learning stoichiometry often presents a challenge for students. Many students tend to be "algorithmic problem solvers" rather than "conceptual thinkers" in chemistry. To address the challenges of learning stoichiometry, current technological advances have begun to offer significant potential for enhancing student understanding. Technological advancements appear to be a lifeline when students encounter difficulties. One such application is the Simple Stoichiometry Calculator App. Stoichiometry calculator apps can help students visualize abstract concepts, solve problems step-by-step, and receive instant feedback. In addition to existing applications, learning through coding can also be an engaging and interactive solution for students. This is because coding not only requires technical skills but also tools for developing logical thinking, problem-solving, and creativity. The integration of coding and chemistry, particularly in the development of a simple stoichiometry calculator application, offers an innovative approach to enhancing classroom learning. In light of the aforementioned issues, a well-designed Simple Stoichiometry Calculator Application is expected to address this need. Therefore, this community service program focused on coding for chemistry has significant potential to improve the quality of chemistry education in schools at the junior high school (SMP) level.